Margaret Chase Smith Essay: High School Student Essay Winners - Parker, Emily; Culley, Rachel; Kirby, Miles (Maine Policy Review, 2003)
Maine has benefited from the public service of many well-respected and influential national leaders over the last two centuries. One of them, Senator Margaret Chase Smith, offered her reflections on leadership at a time when the United States faced a struggle for civil rights at home and the tensions of the Cold War abroad. With the country currently confronting challenges such as the threat of terrorism, ongoing tensions in the Middle East, and the taint of corporate scandals, the Margaret Chase Smith Library annual essay contest invited Maine high school seniors to reflect on the qualities leaders will need to possess in order to be more effective in the twenty-first century. We feature here the three top prize-winning essays by Emily Parker (first), Rachel Culley (second) and Miles Kirby (third).
Keywords: leadership; American politics